Warren Durgin’s Gravestone and the Renewal of American Civic Democracy - Skocpol, Theda (Maine Policy Review, 2002)
In the Margaret Chase smith Essay, Theda Skocpol reflects on the importance of voluntary associations on Maine and national civic life in the past. She notes that the traditional types of voluntary associations have declined since the 1960s, though at the state and local level there are nonprofit organizations with paid staff that provide some of the functions of the older voluntary organizations, and which themselves also use volunteers.
Keywords: Maine; voluntary associations; civic engagement